Are telephone consultations here to stay in rheumatology?. Issue 1 (16th December 2020) - Raizada, Sabrina R; Cleaton, Natasha; Bateman, James; Mulherin, Diarmuid M; Barkham, Nick
Abstract: Objectives: During the COVID-19 pandemic, face-to-face rheumatology follow-up appointments were mostly replaced with telephone or virtual consultations in order to protect vulnerable patients. We aimed to investigate the perspectives of rheumatology patients on the use of telephone consultations compared with the traditional face-to-face consultation. Methods: We carried out a retrospective survey of all rheumatology follow-up patients at the Royal Wolverhampton Trust who had received a telephone consultation from a rheumatology consultant during a 4-week period via an online survey tool. Results: Surveys were distributed to 1213 patients, of whom 336 (27.7%) responded, and 306 (91.1%) patients completed all components of the survey. Overall, an equal number of patients would prefer telephone clinics or face-to-face consultations for their next routine appointment. When divided by age group, the majority who preferred the telephone clinics were <50 years old [χ 2 (d.f. = 3) = 10.075, P = 0.018]. Prevalence of a smartphone was higher among younger patients (<50 years old: 46 of 47, 97.9%) than among older patients (≥50 years old: 209 of 259, 80.7%) [χ 2 (d.f. = 3) = 20.919, P < 0.001]. More patients reported that they would prefer a telephone call for urgent advice (168, 54.9%). Conclusion: Most patients interviewed were happy with their routine face-to-face appointment being switched to a telephone consultation. Of those interviewed, patients >50 years old were less likely than their younger counterparts to want telephone consultations in place of face-to-face appointments. Most patients in our study would prefer a telephone consultation for urgent advice. We must ensure that older patients and those in vulnerable groups who value in-person contact are not excluded. Telephone clinics in some form are here to stay in rheumatology for the foreseeable future.